2016
DOI: 10.2147/lra.s119483
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy of intravenous lidocaine infusion after laparoscopic fundoplication: a prospective, randomized, double-blind, placebo-controlled trial

Abstract: This study aimed to determine if intravenous lidocaine infusion reduces postoperative pain intensity following laparoscopic fundoplication surgery and to also validate the safety of intravenous lidocaine at the dose tested. This was an equally randomized, double-blind, placebo-controlled, parallel-group, single center trial. Adult patients undergoing laparoscopic fundoplication were recruited. The intervention group received 1 mg/kg intravenous lidocaine bolus prior to induction of anesthesia, then an intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Low body weight can result in a reduction in skeletal muscle mass (which normally acts as a storage reservoir for local anaesthetic) and may be associated with an increased frequency of adverse reactions [90]. However, patients with high body mass index (BMI) may also have inadvertently higher plasma concentrations [16, 91]; this may be because actual, rather than ideal, body weight is used for dose calculation. This notion is supported by Dale et al., who showed that patients’ actual plasma concentrations were 20% higher than predicted when actual body weight was used [91].…”
Section: Is Lidocaine Safe?mentioning
confidence: 99%
See 1 more Smart Citation
“…Low body weight can result in a reduction in skeletal muscle mass (which normally acts as a storage reservoir for local anaesthetic) and may be associated with an increased frequency of adverse reactions [90]. However, patients with high body mass index (BMI) may also have inadvertently higher plasma concentrations [16, 91]; this may be because actual, rather than ideal, body weight is used for dose calculation. This notion is supported by Dale et al., who showed that patients’ actual plasma concentrations were 20% higher than predicted when actual body weight was used [91].…”
Section: Is Lidocaine Safe?mentioning
confidence: 99%
“…However, patients with high body mass index (BMI) may also have inadvertently higher plasma concentrations [16, 91]; this may be because actual, rather than ideal, body weight is used for dose calculation. This notion is supported by Dale et al., who showed that patients’ actual plasma concentrations were 20% higher than predicted when actual body weight was used [91]. Some studies have weight exclusions, for example, < 45 kg and > 100 kg [44], which may have reduced the risk of adverse events.…”
Section: Is Lidocaine Safe?mentioning
confidence: 99%
“…Kako lidokain ima manji modulatorni i analgetski potencijal od ketamina i klonidina, zbog različitog mehanizma dejstva, bilo je pokušaja u pronalaženju pozitivnog efekta primenom većih doza od preporučene. Međutim, Dale i saradnici 36 su pokušali da merenjem plazmatske koncentracije lidokaina odrede najoptimalniji odnos doze i efekta. Pozivajući se na ranije publikacije, ovi autori su zaključili da benefit od intraoperativne primene lidokaina imaju samo pacijenti podvrgnuti operacijama na crevima i žučnoj kesi, dok su bez benefita urološke operacije (osim operacija prostate), ginekološke, ortopedske, operacije na srcu i operacije u regiji glave i vrata [37][38][39][40] .…”
Section: Lidokainunclassified
“…A number of authors have confirmed the safety of the postoperative infusion of lidocaine in doses ranging from 3,200mg to 6,000mg over a 48 hour period. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In the past few years, the use of interfacial plane blocks has been more and more advocated, 20 including erector spinae plane blocks (ESPB) for thoracic surgery, [21][22][23][24][25] pectoralis and serratus blocks for breast surgery [26][27][28][29] and quadratus lumborum (QL) blocks for abdominal surgery, 30 Intravenous lidocaine (IV lido) infusions have been demonstrated to be an effective technique for postoperative analgesia in several different types of surgery, including abdominal, [31][32][33][34] thoracic, 35,36 and spine. 37,38 We hypothesized that SNBs followed by IV lido would be as effective as CNBs.…”
Section: Introductionmentioning
confidence: 99%